Fail fast or win big the start-up plan for starting now - Schroeder, Bernhard (AMACOM - American Management Association, 2015)
-- costly. -- connect with real customers and determine quickly whether their idea is -- entrepreneurs who set out to fail fast and ended up winning big, this ground breaking guide reveals how the right kind of risk can really pay off.